Drug utilisation and self medication pattern of anti-fungal drugs in dermatology outpatient department of a tertiary care hospital - Deb, Pooja; Mohanty, Ipseeta; Slathia, Indu; Verma, Vandana (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Fungal infections have become increasingly prevalent. Self-medication is a common health care practice to treat fungal diseases or for symptomatic relief. Because of self-medication drug-sensitive fungal pathogens have gradually developed resistance. Aims and objectives of the study was to define the pattern of antifungal drug use and self-medication pattern for common fungal infections of skin in dermatology outpatient. Methods: The present study was an Observational, descriptive, cross sectional study conducted at Dermatology OPD of MGM Medical College, Kamothe. All adult patients with fungal infections of the skin attending the Dermatology OPD were enrolled. A study performa was specifically designed to record information related to demographic, disease profile and medications prescribed. Results: A total of 200 patient’s prescriptions were analysed. Percentage of drugs prescribed by generic name was found to be 20.26%, Percentage of drugs prescribed from National Essential Drug List 2015 was found to be 79.74%. There were no encounters with antibiotic and parenteral preparations. Only 5.16% of the drugs prescribed were fixed dose combination (FDC) as compared to 94.93% as Monotherapy. Most frequently prescribed anti-fungal agents were the azoles; amongst which Imidazoles (53.33%) were the commonest. Most commonly prescribed individual antifungal was oral Terbinafine (64.81%) and topical was Eberconazole (58.49%). The dosage form most frequently encountered was Cream (92.45%). The prevalence of self-medication for dermatological conditions among patients was 62.26%. Most of the drugs for self-medication were topical (creams) FDC of antifungal and steroids. Around 78% of the self-medication information was obtained from the chemists. Conclusions: The study documented physician preference for Monotherapy than FDC. Prescribers need to be made aware for prescribing generic and essential drugs, thus ensuring rational utilization. They also need to counsel and discourage patients from self-medication.